EFEKTIVITAS PENGAWASAN PEGAWAI DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU DALAM IMPLEMENTASI PERMENDAG NOMOR 67 TAHUN 2018 (STUDI KASUS PASAR LABUH BARU) - Annisa Novtria (Jurnal Sumber Daya Manusia Unggul (JSDMU), 2022)
This research was conducted on employees of the Industry and Trade Office of Pekanbaru City who supervise the implementation of Permendag Number 67 of 2018. The non-conformity of the use of scales by traders causes inaccuracies in measurement. The purpose of this research is to explain the performance of employees of the Department of Industry and Trade of Pekanbaru City in conducting supervision at Labuh Baru Market in accordance with Permendag Number 67 of 2018, as well as factors that hinder the effectiveness of the supervision of employees of the Department of Industry and Trade of Pekanbaru City. The research method used is qualitative with a case study approach, and data is collected through observation, interviews, and documentation. The data were then analyzed using triangulation techniques. The results showed that the supervision carried out by employees of the Pekanbaru City Industry and Trade Office at Labuh Baru Market in accordance with Permendag Number 67 of 2018 was not effective, and there were still obstacles such as inadequate human resources in recalibrating the scales